THE POLICY OF THE SOVIET POWER IN CENTRAL ASIA - Nuridinov Turdali Qambarovich; Hoshimov Dilmurodjon Doniyorjon ugli (Galaxy International Interdisciplinary Research Journal, 2023)
This article highlights the issues of the policy of the Soviet government towards the states of Central Asia at the beginning of the 20th century.